Magnesium Starvation of Aerobacter aerogenes II. Rates of Nucleic Acid Synthesis and Methods for Their Measurement - Kennell, David (1967)
The rates of synthesis of Aerobacter aerogenes nucleic acids were estimated during incubation of the bacteria in a Mg(++)-free medium. Deoxyribonucleic acid (DNA) synthesized during Mg(++) starvation, or in the preceding exponential growth, remained acid-precipitable for 2.5 hr before breaking down to acid-soluble products during a period of many hours. Rates of DNA synthesis were calculated by correcting the net amounts of DNA per milliliter to values that would have appeared had there been no decay. After the first few hours, this rate was constant, the amount of DNA present at the start of Mg(++) starvation being synthesized every 130 min. Rates of synthesis of total ribonucleic acid (RNA) were established in two ways: (i) by measurements of the incorporation of exogeneous uracil and glucose carbon into RNA, and (ii) by the accumulation of transfer RNA (tRNA), since this component is stable during Mg(++) starvation. After the first few hours, this rate was constant, the amount of RNA present at the start of Mg(++) starvation being synthesized about every 120 min. Fractionation by gradient centrifugation revealed that at all times of starvation the ratio of newly synthesized tRNA-rRNA was the same as it was during exponential growth. Furthermore, newly synthesized ribosomal RNA (rRNA) became a part of polysomal structures. Thus, in the absence of Mg(++), DNA, tRNA, and rRNA were synthesized in the same relative proportions as during exponential growth, at rates close to one-half the instantaneous rates of synthesis in the bacteria growing exponentially at the start of starvation.